Financialization and the impasse of capitalism. Issue 1 (3rd April 2019) - Chesnais, François
Abstract: This article considers the inextricable relationship between globalization and financialization. It then argues that the decisive characteristic of financialization is the preeminence of financial accumulation over productive accumulation and of capital-as-property over capital-as-function. The importance of intercorporate power relationships in the distribution of surplus value is demonstrated. After a short setback in 2009, claims to surplus value have continued to grow faster than its production and appropriation, implying that financial profits have become harder to earn. The outcome is the unabated intensity of asset trading and endemic global financial instability.